Advanced Automotive Fault Diagnosis - Denton, Tom. (London : Arnold, 2000)
Diagnostic or fault finding is a fundamental part of an automative technician's work. This advanced text enables students to understand both the theory and practical applications of automotive systems diagnosis.
Includes index.
Keywords: Automobiles -- Maintenance and repair; Transport